Immobilization of Acetylcholinesterase on Screen-Printed Electrodes. Application to the Determination of Arsenic(III) - M. Julia Arcos-Martínez; Olga Domínguez-Renedo; Silvia Sanllorente-Méndez (Sensors, 2010)
Enzymatic amperometric procedures for measuring arsenic, based on the inhibitive action of this metal on acetylcholinesterase enzyme activity, have been developed. Screen-printed carbon electrodes (SPCEs) were used with acetylcholinesterase covalently bonded directly to its surface. The amperometric response of acetylcholinesterase was affected by the presence of arsenic ions, which caused a decrease in the current intensity. The experimental optimum working conditions of pH, substrate concentration and potential applied, were established. Under these conditions, repeatability and reproducibility of biosensors were determined, reaching values below 4% in terms of relative standard deviation. The detection limit obtained for arsenic was 1.1 × 10−8 M for Ach/SPCE biosensor. Analysis of the possible effect of the presence of foreign ions in the solution was performed. The method was applied to determine levels of arsenic in spiked tap water samples.